Development of Islamic Banking in Rajshahi Bangladesh: An Exploratory and Existence Study - Omor Faruk; Mahama-irfan Jehyeh; Mohammad Panah alias Faraz Ahmed; Abdulrohim E-sor; Ishmah Afiyah; Nuha (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to explore the development, effectiveness, and challenges of Islamic banking services in the Rajshahi region and analyze their contribution to economic development, job creation, and social justice. Islamic banking, based on ethical and interest-free principles, has become an integral part of the region's financial landscape. The study also evaluates how Islamic banking aligns with the cultural, ethical, and economic needs of the local community. Theoretical framework: The theoretical framework of this research is grounded in Islamic economic principles, which promote financial inclusion, distributive justice, and ethically driven economic development. Literature Review: Previous literature highlights the potential of Islamic banking to empower communities economically, despite challenges such as limited public awareness, regulatory constraints, and operational limitations. Methods: The study employs a mixed-method approach, combining primary data collected through surveys and interviews, with secondary data analysis of relevant literature. Surveys were conducted with Islamic banking customers in the Rajshahi region, while interviews involved practitioners and experts in the field. Results: The findings reveal that public trust in Islamic banking in Rajshahi is steadily increasing, resulting in a positive impact on regional economic growth. Islamic banking services have proven effective in fostering community economic empowerment and promoting equitable financial practices. However, barriers such as insufficient awareness, regulatory hurdles, and operational infrastructure constraints continue to hinder the full realization of its potential. Implications: The implications of this study emphasize the need for structural reforms to enhance the effectiveness of Islamic banking services. These reforms include improving financial literacy on Islamic banking, streamlining regulations, and strengthening the operational capacity of financial institutions. Novelty: The novelty of this research lies in its integrated analysis of the social, cultural, and economic dimensions of Islamic banking in Rajshahi and its strategic recommendations for maximizing its contribution to sustainable development. This study provides valuable insights for policymakers, financial institutions, and researchers in fostering a robust and inclusive Islamic banking system, ensuring it becomes a key pillar of regional economic development.